Green bonds, air quality, and mortality: Evidence from the People's Republic of China - Yan Luo; Shu Tian; Hao Yang (Asian Development Bank (ADB), 2021)
In this paper, we examine whether and how green bond issuance affects local air quality and mortality rates in the People's Republic of China. We find that a 1 standard deviation increase in corporates' green bond financing in a city is associated with a 0.6% reduction in local air pollution generally and an 0.8% reduction in PM2.5, which refers to tiny pollutant particles with a size of less than 2.5 microns. The effect is stronger when certified green bonds are examined and in cities with higher gross domestic product growth. Further, the green bond financing prevalence is also significantly and negatively associated with local mortality rates, which is consistent with our expectation that, by improving local air quality, green bond issuance helps to enhance local residents' health. The findings are robust to the control of a set of potential determinants of air quality, and a series of robustness tests confirm that the effects are not simply driven by endogeneity.
Keywords: G19; G12; 330; green bonds; air quality; mortality